Retaining Meaning Across Cultures: Larson-Based Analysis on Metaphorical Figurative Language Translation in Coelho’s The Alchemist - Novyana, Novyana; Thohiriyah, Thohiriyah (Jurnal Bahasa dan Sastra, 2025)
The Alchemist by Coelho is a philosophical novel about the journey of a young shepherd named Santiago, who finds a treasure that is hidden near the Egyptian pyramids. The story is rich in metaphor, which makes it an ideal topic for translation studies that focus on cultural nuances and emotional depth. This study aims to examine how Larson’s translation strategies are able to translate significant metaphors while retaining the philosophical and emotional complexity. The data in this study are seven key metaphors that convey the concept of personal destiny, spiritual interconnectedness, personal desire, nature signs, gendered image, and peacefulness. This study uses a qualitative method. By applying the analysis of metaphor translation by Larson, the results indicate that effective translation techniques used by the translator, Lesmana (2005), such as generalisation, omission, amplification, adaptation, and literal translation, not only retain the original meaning of the metaphor but also modify them to align with Indonesian culture. This work provides an understanding of the challenges of translating metaphors, which contributes to broadening the discussion regarding how to convey information effectively across cultures in literary contexts.